Target-to-Distractor Ratio Effects on Decision Time in the Orderly Array Shape Cancellation Task. Issue 2 (October 2013) - Nakajima, Yoshimi; Ikeda, Yoshifumi; Okuzumi, Hideyuki
The cancellation task is a paper-and-pencil test commonly used to assess attention or planning. This study investigated whether the decision time performance on the task was influenced by the number of targets and distractors. This study reduced the demand of planning and used an index of the decision time, an estimate of the time taken to decide whether to mark a stimulus. Forty healthy adults ( M age = 21.3 yr., SD = 1.5) performed five cancellation tasks. Four tasks were conducted with instructions to mark a detected target. The target-to-distractor ratio varied from 35/15, 40/10, 45/5, and 50/0, and one task with instructions to mark all stimuli (50/0), to measure the motor time to mark targets. One-way analysis of variance indicated statistically significant differences between conditions. There was a linear relationship between decision time and target-to-distractor ratio; the decision time increased as the proportion of distractors increased. The results suggested the decision time reflects the frequency of switches between responses to targets and distractors or attention modulation of processing to targets and distractors.